Customs Duty Evasion Issues in Nepal - Maharjan, Gautam (Nepalese Journal of Management Science and Research, 2019)
The main objective of this study is to identify the magnitude of issues relating to customs duty evasion in Nepal. Judgmental sampling technique has been applied with the total of 819 respondents: 421 from business communities and 398 from government officials. Descriptive statistics and compare mean test has been used for the data analysis. From the ranking analy- sis, it is concluded that respondents are more serious on the issue of ‘difficulties in managing open border’, ‘ambiguous customs policy’ and ‘poor infrastructure and inconvenient location’ which were ranked first, second and third respectively. However, the respondents become less serious in the issue of ‘poor technology adoption’ which is ranked last (seventh). The mean scores on each issue were above three and it indicates that the respondents agree on seriousness of the customs duty evasion. However, the mean difference test across business communities and government officials on each issue were found to be significantly different as the mean scores for business communities were higher. Identification of the seriousness on the issues of customs duty evasion in this study could be advantageous for the revenue planner to make newer customs policy.